Temas geradores através de uma abordagem temática freireana como estratégia para o ensino de química e biologia - Miranda, Ana Carolina Gomes (2015)
The methodological foundations of educational concept proposed by Freire are based on dialogicity and problematization about the reality and social contradictions experienced by the students, who are involved on the generating themes. Obtaining a generating theme, according to Freire (2014), occurs through a thematic investigation. Delizoicov (1990) systematized the thematic investigation in five stages: 1st - preliminary survey of reality, 2nd analysis of the situations and choice of encodings, 3rd - circle of thematic investigation, 4th - thematic reduction and 5th - development of the program in the classroom. In this research, we incorporated a 6th stage, which refers to the assessment of learning. In this perspective, the focus of this study was to evaluate the implications of the use of generating themes in the learning of high school students. To do this, firstly, we conducted interviews, visits and researches in educational and government sources. The data were collected through interviews and questionnaires applied to about 150 members of the school community, including high school students, parents, teachers, staff and residents around school environment. From the results of the first and second steps came the following themes: violence, safety, health, drugs, basic sanitation and infrastructure. In the 3rd stage, these issues were discussed with all school community in order to choose the most significant, which was "Drugs". From this generating theme, it was selected, with teachers of Chemistry and Biology, the necessary contents for the interpretation and understanding of this subject (4 th Step - Thematic reduction). From this, we developed two blocks of studies which were applied in two classes of third grade of high school, in a public school in Santa Maria, RS, Brazil. The data in this stage of the research were collected through textual productions, surveys, exercises, construction of Comics Strips (CS) and production of concept maps, and analyzed using content analysis proposed by Bardin (1994). The results of this research demonstrate that the use of the generating theme in the school program structure favors the teaching of Chemistry and Biology, as well as a more critical and citizen education.